Sustainability of intensive beef production system in North-East Italy: relationships between phosphorus supply and productive performance - Berton, Marco; Cesaro, Giacomo; Gallo, Lizeth; Ramanzin, Maurizio; Sturaro, Enrico (Acta Agraria Kaposváriensis, 2014)
The beef sector of the Veneto Region is based on young bulls imported mainly from France and reared intensively using total mixed rations based on maize silage and concentrates. While nitrogen excretion of the sector is regulated by Nitrate Directive, the excretion of phosphorus (P) is less studied, despite of its potentially great impact on environment. This study aims at analysing the relationships between productive and economic performances and P content of the diet in 14 farms of the region. For a whole productive year feed consumption, ingredients and chemical composition of diets were monthly collected. Average Daily Gain (ADG), Feed conversion ratio (FCR), daily gross profit (DGP), and P balance were calculated. ADG, FCR, and DGP were analysed with a mixed model using arrival season, arrival weight, class of dietary content of P, protein and starch as fixed effects and farm as random effect. Average daily gain was 1.39±0.08 kg/d, FCR was 0.14±0.01 kg/kg, and DGP 2.5±0.40 €/d. The P dietary content was on average high (0.38±0.04, % DM), which resulted in P intakes and excretions of 13.49±1.94 and 9.85±1.92 kg/head/place, respectively. None of the productive and economic traits was affected by phosphorus content of the diet. As a consequence, the phosphorus supplementation can be reduced without the risk of weakening productive and economic performances.
Keywords: Beef cattle; intensive farms; environment; Charolais breed; P excretion